Regulatory Affairs endorsement for Fast Track and expedite review with major health authorities. - Sanyam Gandhi, Ajay Sharma, Dr. Anil Kumar Gupta,Dr. Akhilesh Tiwari, Dr. Aakash Singh Panwar (Drugs and Cell Therapies in Hematology, 2021)
Fast track is a process designed to facilitate the development and expedite the review of drugs to treat serious conditions and fill an unmet medical need. The purpose is to get important new drugs to the patient earlier. Fast Track addresses a broad range of serious conditions. Determining whether a condition is serious is a matter of judgment, but generally is based on whether the drug will have an impact on such factors as survival, day-to-day functioning, or the likelihood that the condition, if left untreated, will progress from a less severe condition to a more serious one. AIDS, Alzheimer’s, heart failure and cancer are obvious examples of serious conditions. However, diseases such as epilepsy, depression and diabetes are also considered to be serious conditions. Filling an unmet medical need is defined as providing a therapy where none exists or providing a therapy which may be potentially better than available therapy.